Structural identification of the pacemaker cells and expression of hyperpolarization-activated cyclic nucleotide-gated (HCN) channels in the heart of the wild Atlantic cod, Gadus morhua (Linnaeus, 1758) - Capillo, Gioele; Lauriano, Eugenia Rita; Icardo, Jose Manuel; Siriyappagouder, Prabhugouda; Kuciel, Michal; Karapanagiotis, Stelios; Zaccone, Giacomo; Fernandes, Jorge Manuel de Oliveira (International Journal of Molecular Sciences, 2021)
Hyperpolarization-activated cyclic nucleotide-gated (HCN) channels are proteins that contain highly conserved functional domains and sequence motifs that are correlated with their unique biophysical activities, to regulate cardiac pacemaker activity and synaptic transmission. These pacemaker proteins have been studied in mammalian species, but little is known now about their heart distribution in lower vertebrates and c-AMP modulation. Here, we characterized the pacemaker system in the heart of the wild Atlantic cod (Gadus morhua), with respect to primary pacemaker molecular markers. Special focus is given to the structural, ultrastructural and molecular characterization of the pacemaker domain, through the expression of HCN channel genes and the immunohistochemistry of HCN isoforms, including the location of intracardiac neurons that are adjacent to the sinoatrial region of the heart. Similarly to zebrafish and mammals, these neurons are immunoreactive to ChAT, VAChT and nNOS. It has been shown that cardiac pacemaking can be modulated by sympathetic and parasympathetic pathways, and the existence of intracardiac neurons projecting back to the central nervous system provide a plausible link between them. publishedVersion